Manajemen Pembelajaran Online dalam Meningkatkan Proses dan Hasil Belajar Peserta Didik - Sovitunnizar, Muhammad Rifqi; Slamet, Slamet (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2024)
The purpose of this study is to; first, describe and analyze the management of online learning planning in improving the process and learning outcomes of students. Second, describe and analyze the management of online learning implementation in improving the process and learning outcomes of students. Third, describe and analyze the management of online learning evaluation in improving the process and learning outcomes of students at SMP Cordova Tegalsari Banyuwangi. The approach used in this study is a qualitative approach with a case study type. Data collection techniques used in this study include documentation, observation and interviews. The data analysis technique used in this study is interactive analysis of Miles, Huberman and Saldana, with several steps, reducing data, presenting data and drawing conclusions. While the data validity test uses source triangulation and member check. The results of the study show that; First, based on the analysis of online learning planning management in improving the process and learning outcomes of students, including electronic needs and learning alignment, so that maximum learning outcomes in each subject must be taught by teachers who are qualified and have competence in their fields and schools facilitate teachers to take online learning training; Second, the management of online learning implementation in improving the process and learning outcomes of students must be supported by adequate electronic facilities for teachers and students, teachers prepare several applications that are easily accessible to all students and teachers take training related to the implementation of online learning from schools and the government; Third, online learning evaluation management in improving the process and learning of students by sending files to WhatsApp, Telegram, or other groups then providing instructions via video call, for student attendance guided through video call calls with the help of the Google Form application and to make it easier for students evaluation materials are uploaded on Google sites or YouTube.